Celastrol Downmodulates Alpha-Synuclein-Specific T Cell Responses by Mediating Antigen Trafficking in Dendritic Cells - Ng, Lam; Wang, Xiaohui; Yang, Chuanbin; Su, Chengfu; Li, Min; Cheung, Allen Ka Loon (Frontiers in Immunology, 2022)
Parkinson’s Disease (PD) is a neurodegenerative disease that affects the elderly. It is associated with motor dysfunction due to the accumulation of misfolded or aggregated fibrillar alpha-synuclein (α-syn) in the mid-brain. Current treatments are mainly focused on relieving the symptoms but are accompanied by side effects and are limited in halting disease progression. Increasing evidence points to peripheral immune cells underlying disease development, especially T cells contributing to α-syn-related neuroinflammation in PD. The onset of these cells is likely mediated by dendritic cells (DCs), whose role in α-syn-specific responses remain less studied. Moreover, Traditional Chinese medicine (TCM)-derived compounds that are candidates to treat PD may alleviate DC-T cell-mediated immune responses. Therefore, our study focused on the role of DC in response to fibrillar α-syn and subsequent induction of antigen-specific T cell responses, and the effect of TCM Curcumin-analog C1 and Tripterygium wilfordii Hook F-derived Celastrol. We found that although fibrillar α-syn did not induce significant inflammatory or T cell-mediating cytokines, robust pro-inflammatory T cell responses were found by co-culturing fibrillar α-syn-pulsed DCs with α-syn-specific CD4+ T cells. Celastrol, but not C1, reduced the onset of pro-inflammatory T cell differentiation, through promoting interaction of endosomal, amphisomal, and autophagic vesicles with fibrillar α-syn, which likely lead to its degradation and less antigen peptides available for presentation and T cell recognition. In conclusion, regulating the intracellular trafficking/processing of α-syn by DCs can be a potential approach to control the progression of PD, in which Celastrol is a potential candidate to accomplish this.